The diplomats : 1939 - 1979 - Craig, Gordon Alexander 1913-2005 Hrsg; Loewenheim, Francis L. Hrsg (Princeton Univ. Press, 1994)
Diplomats and diplomacy during the second world war / Gordon A. Craig -- The U.S. Department of State from Hull to Acheson / Richardson Dougall -- His master's voice : Viacheslav Mikhailovich Molotov as Stalin's foreign commissar / Steven Merritt Miner -- Ernest Bevin and British foreign policy, 1945-1951 : Geoffrey Warner -- The moralist as pragmatist : John Foster Dulles as cold war strategist / Richard D. Challener -- The road to Suez : the British foreign office and the Quai d'Orsay, 1951-1957 / Victor H. Feske -- Konrad Adenauer and his diplomats / Gordon A. Craig -- The foreign policy of Charles de Gaulle / Stanley Hoffmann -- Jean Monnet : the innovator as diplomat / W.W. Rostow -- Adam Rapacki and the search for European security / Piotr Wandycz -- Japan returns to the world : Yoshida Shigeru and his legacy / Akira Iriye -- In the shadow of Mao : Zhou Enlai and new China's diplomacy / Shu Guang Zhang -- Nehru and the diplomacy of nonalignment / Rena Fonseca -- Eban and Israeli foreign policy : diplomacy, war, and disengagement / Michael Brecher -- Sadat : the calculus of war and peace / Raphael Israeli